IBX-mediated oxidative addition of isocyanides to cyclic secondary amines: total syntheses of alangiobussine and alangiobussinine. Issue 73 (21st August 2019) - Ambule, Mayur D.; Tripathi, Shashank; Ghoshal, Anirban; Srivastava, Ajay K.
Abstract : An efficient method for synthesizing C(1)-carboxamides through IBX-mediated oxidative addition of isocyanides to cyclic secondary amines has been reported. Abstract : The present study describes a robust and general method for the synthesis of C(1)-carboxamides through IBX-mediated oxidative addition of isocyanides to tryptolines and 1, 2, 3, 4-tetrahydroisoquinolines. In this transformation, IBX plays a dual role of an oxidant and Lewis acid to activate imine facilitating isocyanide addition. Detailed mechanistic investigations were performed by isotopic labeling and real-time NMR experiments. The method was utilized for the gram scale syntheses of two alkaloids alangiobussine and alangiobussinine in 63% and 45% overall yield, respectively.